The Health in the Value System of Russian Youth: Contradictory Discursive Practices - Vangorodskaya, Svetlana A.; Babintsev, Valentin P.; Shmarion, Yuri V.; Konev, Ivan V.; Nadutkina, Irina E. (International Journal of Criminology and Sociology, 2022)
The axiological aspects of the self-preserving behaviour of Russian youth are considered on the basis of the data of sociological studies. The contradiction between the high value of health in the minds of modern youth declared and the underdevelopment of daily practices aimed at its preservation and strengthening is revealed. The probable causes of the contradiction are listed; they are related as to the specifics of this socio-demographic group, to its hedonistic orientation, to situational orientation of thinking, and also to the limited capacity of youth in relation to receiving medical and preventive services. Conclusion was made that it is necessary to form the axiological-and-motivational foundations of self-preserving behaviour of Russian youth as one of the most important directions in the implementation of the state policy to protect public health in general.